Aproveitamento de resíduos para aumento da eficiência energética industrial - Carstens, Luciano (2021)
Enabling sustainable development is one of the main challenges to be overcome by nations and future generations. The planet does not have enough natural resources to maintain the pace of consumption in current standards and at the same time guarantee the quality of life for the population. Therefore, the search for sustainability must occur at all levels and sectors of society, in communities, in services and especially in production and transformation processes. To achieve sustainable development, it is necessary to balance economic, social, and environmental interests with the availability of resources, in addition to fostering new technologies that assist in this process. It is necessary to understand the entire production cycle, from the extraction processes of the raw material to the stages of transformation, use, disposal, and post-disposal of products. This involves the waste generated and the energy resources spent over the entire life cycle. The present thesis demonstrates how the concepts of circular economy can be used to increase industrial energy efficiency. To this end, the study is based on five distinct theoretical perspectives: Material Flow Analysis (AFM), Product Life Cycle (CVP), Symbiosis or Industrial Ecology (EI), Circular Economy (EC) and Energy Efficiency in Industry. To carry out these studies, visits and interviews were carried out in one of the largest vehicle industries in Brazil, Renault do Brasil at the Airton Senna Complex and as a result it was possible to carry out a case study enabling the project and the implementation of a system for using biomass from packaging waste to replace natural gas, saving money, increasing energy efficiency and decreasing the carbon footprint during the production process. The result of this implementation allowed the Renault do Brasil plant to become the most efficient of the group in terms of energy consumption per vehicle produced, as can be highlighted in the annual sustainability report presented by it in 2020, generating savings in natural gas consumption of 7.2% in the manufacture of passenger cars and 13.9% in the manufacture of commercial vehicles, this in the first year of implementation of the new process. This model of reuse of waste, developed and implemented with success and originality, contributes as inspiration for other industries in the same sector and other segments that have similar problems in energy consumption and that bring opportunities for the use of waste as energy resources, with minor adaptations in developed solution.